Pengaruh kualitas sumber daya manusia, pengendalian internal, dan teknologi informasi terhadap keandalan laporan keuangan pada skpd provinsi riau - Wulandari, Putri; Savitri, Enni; ', Kennedy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze the quality of human resources Influence of the reliability of the financial statements in Riau province on education, then Effect of Internal Control of the reliability of the financial statements in Riau province on education, and the Effect of Information Technology on the reliability of the financial statements in Riau province on education.The population in this study is the Regional Working Units (on education) in the Riau provincial government. Riauberjumlah on education in 38 provinces comprising Region 1 Secretariat Riau, Riau Province Inspectorate 1, 1Sekretaris DPRD Riau, Riau KORPRI 1 Secretary, Civil Service Police Unit 1, 2 Hospital (Hospital and RSJ), Agency 14, and 17 Department. Samples from this study are echelon III and IVdi Department and Agency of Riau Province by 86 people. Analysis of the data in this study using tools SPSS software version 17.The results showed that the quality of Human Resources, Internal Control, and Information Technology affect the Reliability of Financial Statements.Keywords: Quality of Human Resources (HR), Internal Control, and Information Technology Against Reliability of Financial Statements